Distinguishing Clinical Enterococcus faecium Strains and Resistance to Vancomycin Using a Simple In-House Screening Test - Natkamon Saenhom; Parichart Boueroy; Peechanika Chopjitt; Rujirat Hatrongjit; Anusak Kerdsin (MDPI AG, 2022)
Vancomycin-resistant enterococci (VRE) are a major concern as microorganisms with antimicrobial resistance and as a public health threat contributing significantly to morbidity, mortality, and socio-economic costs. Among VREs, vancomycin-resistant Enterococcus faecium (VREfm) is frequently isolated and is resistant to many antibiotics used to treat patients with hospital-acquired infection. Accurate and rapid detection of VREfm results in effective antimicrobial therapy, immediate patient isolation, dissemination control, and appropriate disinfection measures. An in-house VREfm screening broth was developed and compared to the broth microdilution method and multiplex polymerase chain reaction for the detection of 105 enterococci, including 81 VRE isolates (61 E. faecium, 5 E. faecalis, 10 E. gallinarum, and 5 E. casseliflavus). Verification of this screening broth on 61 VREfm, 20 other VRE, and 24 non-VRE revealed greater validity for VREfm detection. The accuracy of this broth was 100% in distinguishing E. faecium from other enterococcal species. Our test revealed 93.3% accuracy, 97.5% sensitivity, and 79.2% specificity compared with broth microdilution and PCR detecting van genes. The kappa statistic to test interrater reliability was 0.8, revealing substantial agreement for this screening test to the broth microdilution method. In addition, the in-house VREfm screening broth produced rapid positivity after at least 8 h of incubation. Application of this assay to screen VREfm should be useful in clinical laboratories and hospital infection control units.